Trend in the study of intercultural competence: bibliometric analysis by citespace - Ruiyang, Ren (Association Res Militaris, 2022)
The literature search has shown that the number of research materials associated with intercultural competence has been increasing gradually over the past twenty years. And this apparently shows that a systematic review of intercultural competence is essential for researchers and the aim of this paper is to discuss the trend of transition in intercultural communication studies from the notion of “intercultural competence”, followed by “intercultural communication competence” and the latest notion is “intercultural communicative competence”. In doing so, the Scopus database was adopted, by which the analysis was carried out on the keywords and their diachronic development with retrieval of materials published with the keywords used were “intercultural communication competence” or “intercultural communicative competence” by periodicals from 1970 to 2021. The findings show that the acronym ICC is used to represent all the three notions. Most importantly, the three representative notions emerge in different time but with continuous trait in the study of intercultural communication. Further, the main research aspects are identified in the domain of “education”, involving in “higher education”, “student”, and “human experiment” as well as “study abroad”. The findings of bibliometric analysis provide a more specific insights into the term selection of intercultural communicative competence, its main research aspects, diachronic development and future research direction.